Knowledge regarding antibiotic use among students of three medical schools in Medellin, Colombia: a cross-sectional study (2020)
Background: The objective of the present study was to describe the knowledge regarding the antibiotic therapy of students of three medical schools in Medellín, Colombia. Methods: The study population comprised medical students who were enrolled in three universities. The instrument contained questions regarding their current academic term, the university, the perceived quality of the education received on antibiotic therapy and bacterial resistance, and specific questions on upper respiratory tract infections, pneumonia, urinary tract infections, and skin and soft tissue infections. The information was analyzed by calculating frequencies and measures of dispersion and central tendency. Knowledge regarding the treatment for each type of infection was compared using the Mann–Whitney U test and the Kruskal–Wallis H test. Results: We included 536 medical students, of which 43.5% students consider that the university has not sufficiently trained them to interpret antibiograms and 29.6% students consider that the quality of information received on the subject at their university ranges from regular to poor. The mean score for knowledge regarding antibiotic therapy for upper respiratory tract infections was 44.2 (9.9) on a scale from 0 to 100. The median score with regard to the treatment of pneumonia was 52.9 (14.7), that of urinary tract infection was 58.7 (14.8), and that of skin and soft tissue infections was 63.1 (19.4). The knowledge regarding antibiotic therapy for upper respiratory tract infections, pneumonia, and urinary tract infection does not improve with the academic term, the university, or perceived quality of the education received. Conclusion: A large proportion of medical students perceive that the training received from the university is insufficient with regard to antibiotic use and bacterial resistance, which is consistent with the limited knowledge reflected in the selection of antibiotic treatment for respiratory, urinary tract, and skin and soft tissue infections. Overall, the situation was identical among all universities, and it did not significantly increase with the completion of an academic term.